Professional applied physical training of future specialists of agricultural production - Y.A. Karabanov (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose : develop and experimentally prove the contents, methods and forms of physical training of future specialists of agricultural production. This takes into account advanced course of professional applied physical preparation means kettlebell sport. Material : The study involved 141 students. Duration of study is 5 years. Results : It was found that a significant increase in indicators of flexibility, strength, coordination abilities of students promoted the use of exercises using weights of different weights. Confirmed the legitimacy of the use of such means of physical education for the development of muscle strength of the upper body, back, legs, abdominals. These muscles are the most loaded in the performance of professional activities of mechanical engineers. Conclusions : The program meets the basic criteria for the formation of curriculum for physical education. The program promotes the development of professional applications of physical qualities, motor skills and improve physical performance of students.